Frequent, short bouts of light-intensity exercises while standing decreases systolic blood pressure: Breaking Up Sitting Time after Stroke (BUST-Stroke) trial. Issue 9 (December 2018) - English, Coralie; Janssen, Heidi; Crowfoot, Gary; Bourne, Josephine; Callister, Robin; Dunn, Ashlee; Oldmeadow, Christopher; Ong, Lin K; Palazzi, Kerrin; Patterson, Amanda; Spratt, Neil J; Walker, FR; et al.
Background: Stroke survivors sit for long periods each day. Uninterrupted sitting is associated with increased risk of cardiovascular disease. Breaking up uninterrupted sitting with frequent, short bouts of light-intensity physical activity has an immediate positive effect on blood pressure and plasma clotting factors in healthy, overweight, and type 2 diabetic populations. Aim: We examined the effect of frequent, short bouts of light-intensity physical activity on blood pressure and plasma fibrinogen in stroke survivors. Methods: Prespecified secondary analyses from a three-armed randomized, within-participant, crossover trial. Participants were 19 stroke survivors (nine female, aged 68 years old, 90% able to walk independently). The experimental conditions were sitting for 8 h uninterrupted, sitting with 3 min bouts of light-intensity exercise while standing every 30 min, or sitting with 3 min of walking every 30 min. Blood pressure was measured every 30 min over 8 h and plasma fibrinogen at the beginning, middle, and end of each day. Intention-to-treat analyses were performed using linear mixed models including fixed effects for condition, period, and order, and a random intercept for participant to account for repeated measures and missing data. Results: Sitting with 3 min bouts of light-intensity exercise while standing every 30 min decreased systolic blood pressure by 3.5 mmHg (95% CI 1.7–5.4) compared with sitting for 8 h uninterrupted. For participants not taking antihypertensive medications, sitting with 3 min of walking every 30 min decreased systolic blood pressure by 5.0 mmHg (95% CI −7.9 to 2.0) and sitting with 3 min bouts light-intensity exercise while standing every 30 min decreased systolic blood pressure by 4.2 mmHg (95% CI −7.2 to −1.3) compared with sitting for 8 h uninterrupted. There was no effect of condition on diastolic blood pressure (p = 0.45) or plasma fibrinogen levels (p = 0.91). Conclusion: Frequent, short bouts of light-intensity physical activity decreases systolic blood pressure in stroke survivors. However, before translation into clinical practice, the optimal duration and timing of physical activity bouts needs to be determined. Clinical trial registration: Australian and New Zealand Clinical Trials Registryhttp://www.anzctr.org.au ANZTR12615001189516.